ApoER2: Functional Tuning Through Splicing - Gallo, Christina M.; Ho, Angela; Beffert, Uwe (Frontiers in Molecular Neuroscience, 2020)
Alternative splicing occurs in over 95% of protein-coding genes and contributes to the diversity of the human proteome. Apolipoprotein E receptor 2 (apoER2) is a critical modulator of neuronal development and synaptic plasticity in the brain and is enriched in cassette exon splicing events, in which functional exons are excluded from the final transcript. These alternative splicing events affect apoER2 function, as individual apoER2 exons tend to encode distinct protein functional domains. Although several apoER2 splice variants have been characterized, much work remains to understand how apoER2 splicing events modulate distinct apoER2 activities, including ligand binding specificity, synapse formation and plasticity. Additionally, little is known about how apoER2 splicing events are regulated. Often, alternative splicing events are regulated through the combinatorial action of RNA-binding proteins and other epigenetic mechanisms; however, the regulatory pathways corresponding to each specific exon are unknown in most cases. In this mini-review, we describe the structure of apoER2, highlight the unique functions of known isoforms, discuss what is currently known about the regulation of apoER2 splicing by RNA-binding proteins and pose new questions that will further our understanding of apoER2 splicing complexity.